PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE INDEX CARD MATCH TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA PADA KONSEP KOMPONEN EKOSISTEM - Rahmawati, Susi; Dadi, Dadi (Bioed : Jurnal Pendidikan Biologi, 2019)
This study aim to determine the effect of the implementation of Cooperative Learning Model of Index Card Match Type on Student Activity and Learning Outcomes in the Sub Material of Ecosystem Components. This research method is a quasi experiment with two groups pretest posttest design. The technique of determining the sample using purposive sampling. The samples used are class X-10 and class X-3. The research instrument used observation sheets in the form of rubrics for learning activities and multiple choice questions for student learning outcomes tests. Analysis of the data used is the t test and Wilcoxon test for student learning activities. The results of the study concluded that there was an effect of the application of Cooperative Learning Model of Index Card Match Type to the activities and student learning outcomes in the Sub Material of Ecosystem Components. Keywords: cooperative learning model of index card match type, learning activities, learning outcomes.